Youth and resilience: how to grow inner strength in the modern world - Sodolevska Валерія (Psychosomatic Medicine and General Practice, 2024)
This text is the abstract of the report to the III Scientific and Practical Conference with International Participation "Psychiatry, Narcology, Clinical Psychology and General Medical Practice: Interdisciplinary Issues of the Present", March 22-23, 2024, Kyiv - online.